Wi-Fi (802.11b) and Bluetooth enabling coexistence. - Lansford, J.
This article provides an introduction to issues of coexistence between Bluetooth and Wi-FiTM (IEEE 802.11b), with particular attention to scenarios requiring simultaneous operation, or Sim-OPTM, of both systems in very close proximity. The article explains basic interference mechanisms and quantifies their impact through both actual measurements and simulation. We have developed a detailed simulator that fully models behavior of the physical layer (PHY) and media access control (MAC) of both Bluetooth and 802.11b; it is used to expand the analysis and project the mutual impact of collocated Bluetooth and 802.11b systems across a number of geometries, system parameter settings, and design choices, complementing efforts within the IEEE 802.15.2 Task Group, which are also discussed. The article concludes with a discussion of techniques with the potential to greatly improve the performance of collocated Bluetooth and Wi-Fi systems. A key result of this investigation is that while performance of both systems can degrade when they are collocated, a number of techniques can be employed to virtually eliminate the problems
Keywords: 802.11b systems; Bluetooth; IEEE 802.11b.; IEEE 802.15.2 Task Group; ISM band; MAC; RFI; Sim-OP.; Wi-Fi system; Computer model; Interference mechanisms; Measurements; Media access control; Noise; Physical layer; Simulation; Simulator; Simultaneous operation; System design; System geometries; System parameter; System performance; Wireless LAN; Wireless personal area network